Experimental evaluation of MPC-based anti-surge and process control for electric driven centrifugal gas compressors. (October 2015) - Cortinovis, A.; Ferreau, H.J.; Lewandowski, D.; Mercangöz, M.
Abstract : Highlights: Experimental compressor rig for anti-surge and process control investigations. Centrifugal gas compressor modeling, parameter identification and model validation. Anti-surge and process control for electric driven centrifugal gas compressors. MPC formulation and implementation for anti-surge and process control. Proof of concept and comparison to current industry practice on experimental setup. Abstract: The present work concerns model predictive control (MPC) of centrifugal gas compressors and describes the development of an MPC application for the tasks of anti-surge and process control. More specifically, the MPC formulation focuses on the question of how the transient manipulation of driver torque can be used to improve the performance of anti-surge and process control. For the purpose of testing and validating the proposed control algorithm, an experimental compressor test rig is presented, which is designed to mimic a typical centrifugal compressor application in the oil and gas industry. Modeling and parameter identification of the experimental setup is followed by the realization of the MPC solution on an embedded system to comply with the stringent real-time requirements for anti-surge control. Testing is performed with experiments using suction and discharge side disturbances, which are created by rapid valve closures. For comparison the same tests are repeated with conventional control approaches. The test results indicate improvements in maintaining the distance to surge by up to 11%, while at the same time reducing the process control settling time by up to 50%.